Allium species poisoning in dogs and cats - Salgado, B. S. [UNESP]; Monteiro, L. N. [UNESP]; Rocha, Noeme Sousa [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Dogs and cats are the animals that owners most frequently seek assistance for potential poisonings, and these species are frequently involved with toxicoses due to ingestion of poisonous food. Feeding human foodstuff to pets may prove itself dangerous for their health, similarly to what is observed in Allium species toxicosis. Allium species toxicosis is reported worldwide in several animal species, and the toxic principles present in them causes the transformation of hemoglobin into methemoglobin, consequently resulting in hemolytic anemia with Heinz body formation. The aim of this review is to analyze the clinicopathologic aspects and therapeutic approach of this serious toxicosis of dogs and cats in order to give knowledge to veterinarians about Allium species toxicosis, and subsequently allow them to correctly diagnose this disease when facing it; and to educate pet owners to not feed their animals with Alliumcontaing food in order to better control this particular life-threatening toxicosis.
Keywords: Allium spp.; poisonous plants; hemolytic anemia; Heinz bodies